2020
DOI: 10.1101/2020.03.20.999680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ammonia-based enrichment and long-term propagation of zone I hepatocyte-like cells

Abstract: Zone I and zone III hepatocytes metabolize ammonia through urea cycle and drug by cytochrome P450, respectively. Ammonia has a cytotoxic effect, and can therefore be used as a selection agent for enrichment of hepatocytes. Besides, isolated hepatocytes from livers can be propagated ex vivo under appropriate condition. However, it has not been investigated so far whether ammonia-treated hepatocyte-like cells are able to proliferate in vitro. In this study, we employed the ammonia selection strategy to purify he… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In this study, the establishment of a culture system to stably grow DILI patient-derived hepatocytes enabled us to elongate hepatocyte lifespan to more than 30 population doublings with the maintenance of hepatic progenitor progenitor-like phenotypes. Usage of Wnt3a/R-Spondin 1 in combination with the feeder cells for elongation of hepatocyte lifespan is in line with the previous report that WNTs are important for liver regeneration and in vitro propagation of hepatocytes and that irradiated MEFs are useful for maintaining the expression and proliferative capacity of hepatic progenitors [20,32,33].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the establishment of a culture system to stably grow DILI patient-derived hepatocytes enabled us to elongate hepatocyte lifespan to more than 30 population doublings with the maintenance of hepatic progenitor progenitor-like phenotypes. Usage of Wnt3a/R-Spondin 1 in combination with the feeder cells for elongation of hepatocyte lifespan is in line with the previous report that WNTs are important for liver regeneration and in vitro propagation of hepatocytes and that irradiated MEFs are useful for maintaining the expression and proliferative capacity of hepatic progenitors [20,32,33].…”
Section: Discussionsupporting
confidence: 87%
“…Ammonia has been used as a selection agent for enrichment of hepatocytes because of its cytotoxic effect (Tanimizu et al, 2016; Tomotsune et al, 2016; Tsuneishi et al, 2021). Puromycin has been used to select pluripotent stem cell-derived hepatocytes with a high expression of CYP3A4 (Miyata et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Puromycin equalized hepatocytes with diverse functions such as drug metabolism after the in vitro propagation. The stable proliferative capacity of primary hepatocytes and pluripotent stem cell-derived hepatocytes requires WNT, R-sponsin1, and feeder cells 23,[33][34][35][36] . Resistance to puromycin may be due to the high metabolic activities of CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue that arises when considering the clinical application of regenerative medical products is how to prepare large quantities of cells quickly. SEES2 cells, a strain of human embryonic stem cells, are starting to be used in clinical practice [7,8]. Akutsu et al have studied a culture system without animal-derived components, and have reported that it is possible to culture cells stably in that culture system [9].…”
Section: Discussionmentioning
confidence: 99%
“…The SEES2 cell line, an hESC lines, has been established at the National Center for Child Health and Development (NCCHD) for clinical applications and regenerative medicine research [6]. The SEES cell lines are presently being applied in clinical practice, including successful clinical trials in congenital urea cycle disorders [7,8]. It is necessary to establish a safer and more stable method of culturing SEES2 cells for clinical applications in the future.…”
Section: Introductionmentioning
confidence: 99%